" تقدير حقل سرعة الرياح في المياه الاقليمية السورية بالاعتماد على معطيات محطة رصد فوق اليابسة " - داوود صلاح (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم البحث دراسة تحليلية وحسابية لسرعة الرياح فوق البحر على ارتفاعات مختلفة بهدف تقدير حقل الرياح في عرض الشاطئ السوري، بالاعتماد على بيانات محطة رصد جوية متوضعة على اليابسة جنوب مدينة طرطوس، وكذلك حساب متوسط كثافة استطاعة الرياح المتاحة ومتوسط الاستطاعة الكهربائية الفعلية الناتجة عند ارتفاع معين، وبالتالي العمل على إقامة مزارع ريحية في عرض البحر في المياه الإقليمية السورية والاستفادة من الطاقة المتاحة. This paper provides an analytic and enumerative study of wind speed above the sea on different heights for the purpose of evaluating the wind field in Syrian legal water depending on observation station data located in the south of Tartous city. It also calculates the average of wind power density available in the research site and the average of Active electrical power at the same height. Consequently this will lead to build up wind Farms in the sea to generate clean electrical power.